Pharmaceutical Care Workload and Human Resources Requirements at MOH Primary Health Care Center Over Nine years Mass Gathering Hajj (2006-2014) in Al-Medina Region, Saudi Arabia - Alomi, Yousef Ahmed; Alhennawi, Khairat; Khayayt, Nizar (Journal of Pharmacy Practice and Community Medicine)
Purpose: To explore the pharmacy services workload analysis and workforce requirements at Ministry of Health Primary care center during mass gathering Hajj nine years (2006-2014) in Al-Medina Region, Saudi Arabia. Methods: It is a retrospective analysis of nine years (2006-2014) of primary care center pharmacies workload during mass gathering Hajj period. The duration of workload collection was 15-30 days. The pharmacist and pharmacy technicians provide pharmaceutical to all patients either Pilgrim or not Pilgrim at Al-Medina region. The workforce requirements calculated based on MOH workforce standards per primary care centers (PCC), the workload drives as central pharmacy services, patient specific pharmacy activities, and general administration specific pharmacy activities. Results: The total number of Pilgrims (1,952,817-3,161,573) with average (2,445,208) and with an average of (210,765.91) pilgrims visited each primary care center. The average number of pharmacist needed based on MOH standard was (66.67 FTE), while the mean number pharmacist required based on workload was (1,183.99 FTE). It is (17.76 fold) more incremental than MOH pharmacist workforce standards. Conclusion: The pharmacy workload analysis reflects the real demand of pharmacist during mass gathering Hajj period in Al-Medina Region. Targeting to update the MOH standards of primary care center pharmacy workforces during mass gathering Hajj time is required in Al-Madina region in Saudi Arabia.
Keywords: Pharmaceutical Care; Workload; Workforces; Primary Care Center; Mass Gathering; Hajj; Al-Medina; Ministry Of Health; Saudi Arabia